Using Artificial Intelligence Tool in Studying English Skills in Vietnam – An Experimental Research for Vietnamese High School Students - Quyet, Chu Ba; Minh, Nguyen Binh; Anh , Nguyen Phan (Journal of Ecohumanism, 2024)
Artificial Intelligence tools such as Grammarly and ChatGPT are used in the learning process, including learning foreign languages for high school students. This paper aims to synthesize the benefits and limitations of using AI in learning foreign languages, and the current situation of using AI tools in studying English for high school students in Vietnam. The authors have systematized theories about the benefits and limitations of using AI tools in learning English in about 30 papers in peer-reviewed journals from 2018 to 2024. The authors developed a survey to collect data from 300 students in high school at Hanoi in Vietnam to see and know the current status of using AI tools in learning English. The results of data analysis from 297 responses calculated the AI ​​usage situation as follows: Using AI tools in studying English students is very common with a high frequency of use including four skills listening, speaking, reading, and writing. Most of the students are also well aware of the benefits and limitations of AI tools. However, students' use of AI tools is still spontaneous and not supported by teachers and schools. To better use AI for students' English learning, the article makes recommendations to schools and teachers.